Modifikasi Metode Kalium Bikromat Untuk Uji Kualitatif Alkohol Dalam Urine - Ayu Nurislami Wulandari (Universitas Muhammadiyah Surabaya, 2023)
Alcohol is a psychoactive substance that can cause dependence. Alcohol as an intoxicant can affect various structures and processes in the central nervous system and increase the risk of intentional and unintentional injury. One of the direct risks due to alcohol consumption is an accident while driving a vehicle and accidents at work. Rate alcohol It is measured in various body fluids including urine. This study aims to determine the sensitivity of the modified potassium dichromate method for qualitative test of alcohol in urine without filter paper and water bath. This research is a laboratory experimental study, the data obtained were analyzed in a descriptive way, namely seeing the color change of the reaction between the alcohol sample in urine and the Potassium bichromate reagent to green or blue with a modified working method. Tested all showed positive results with the modified Potassium bichromate method. A color change from green to blue is read as a positive alcohol result. The conclusion of this study is that the modified Potassium bichromate method is effective for the qualitative alcohol test process and there is an increase in the sensitivity of the test.